2021
DOI: 10.1186/s12888-020-03021-0
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and acceptability of parent-only group cognitive behavioral intervention for treatment of anxiety disorder in children and adolescents: a meta-analysis of randomized controlled trials

Abstract: Background Anxiety disorder is the most prevalent mental disorder among children and adolescents, causing significant psychosocial problems and physical health conditions. Cognitive behavioral therapy (CBT) is an effective treatment for anxiety disorder in children and adolescents. And parent-only CBT is an alternative treatment for childhood anxiety disorder, which includes psychologists and parents rather than children in the treatment. As a new type of CBT, parent-only CBT has some advantage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…People with anxiety disorders usually have recurring intrusive thoughts or concerns and may have physical symptoms such as sweating, trembling, dizziness or a rapid heartbeat. Anxiety disorders are often the first presentation of psychopathology in youth and are considered the most common psychiatric disorders in children and adolescents [ 1 4 ]. Globally, anxiety is the ninth leading cause of illness and disability among adolescents aged 15–19 years and sixth among those aged 10–14 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with anxiety disorders usually have recurring intrusive thoughts or concerns and may have physical symptoms such as sweating, trembling, dizziness or a rapid heartbeat. Anxiety disorders are often the first presentation of psychopathology in youth and are considered the most common psychiatric disorders in children and adolescents [ 1 4 ]. Globally, anxiety is the ninth leading cause of illness and disability among adolescents aged 15–19 years and sixth among those aged 10–14 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent research proposes parents as change agents in addressing child internalizing symptoms through alternative approaches beyond those designed for externalizing issues (45)(46)(47)(48). Parent-led cognitive behavioral therapy (CBT), in which parents are empowered to implement strategies in their child's daily life, has been found to be effective (45,49). Furthermore, a new research area underscores the substantial role of parental accommodation in perpetuating anxiety symptoms (50,51).…”
Section: Background For the Sparck Contentmentioning
confidence: 99%
“…A further review found that very small benefits for anxiety symptoms were maintained until 12 months in Parent-only CBT was effective in reducing anxiety, comparable to programs involving both children and parents. Parent-directed CBT may be more suitable for younger children, but dropout rates tend to be higher in parent-only programs (Yin et al 2021). Other reviews have shown that parental involvement is not necessarily beneficial in the treatment of anxiety (Cordier et al 2021;Peris et al 2021;Wergeland et al 2021).…”
Section: Evidence From Global Reviewsmentioning
confidence: 99%